Response of levels of potassium and sulphur on yield and yield attributes of summer sesame (Sesamum indicum L.): RESPONSE OF LEVELS OF POTASSIUM AND SULPHUR ON YIELD AND YIELD ATTRIBUTES OF SESAME - K F SATASHIYA; V R AKABARI; V N GOHIL (Journal of Oilseeds Research, 2026)
A field experiment was conducted during the summer seasons of 2019-2022 at the Agricultural Research Station, Junagadh Agricultural University, Amreli, Gujarat, to study the response of summer sesame to different levels of potassium and sulphur. The experiment was laid out in a factorial randomized block design with four replications. The treatments consisted of three levels of potassium (0, 20, and 40 kg K₂O/ha) and three levels of sulphur (0, 10, and 20 kg S/ha). The results revealed that the application of 40 kg K₂O/ha significantly increased seed yield (1315 kg/ha), stover yield (2239 kg/ha), oil yield (630 kg/ha), and most yield-attributing traits compared with the lower potassium levels. Similarly, the application of 20 kg S/ha recorded significantly higher seed yield (1297 kg/ha), stover yield (2220 kg/ha), and oil yield (684 kg/ha). The interaction effects of potassium and sulphur were non-significant. The highest net return (`49,953/ha) and benefit-cost ratio (2.17) were obtained with the application of 40 kg K₂O/ha, while 20 kg S/ha recorded the highest net return (`46,994/ha) among the sulphur levels. The study concluded that the application of 40 kg K₂O/ha and 20 kg S/ha, along with the recommended doses of nitrogen and phosphorus, is optimum for summer sesame cultivation under the North Saurashtra conditions.